2010
DOI: 10.1177/0269881110382467
|View full text |Cite
|
Sign up to set email alerts
|

Acute and subchronic effects of bilastine (20 and 40 mg) and hydroxyzine (50 mg) on actual driving performance in healthy volunteers

Abstract: Bilastine is a new second-generation H1 antagonist. Although bilastine has been demonstrated to produce little or no performance impairment in laboratory tests, it cannot be excluded that it produces impairments in real-life performance such as driving. This study aims to assess the effects of two doses of bilastine (20 and 40 mg) on actual driving after single and repeated administration. Hydroxyzine 50 mg was included as an active control. Twenty-two participants (11 females, 11 males) were tested in a place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 26 publications
0
30
0
1
Order By: Relevance
“…After 8 days of treatment with hydroxizine 50 mg driving performance was still impaired, but to a lesser extent (Conen et al 2010).…”
Section: First Generation Antihistaminesmentioning
confidence: 88%
See 1 more Smart Citation
“…After 8 days of treatment with hydroxizine 50 mg driving performance was still impaired, but to a lesser extent (Conen et al 2010).…”
Section: First Generation Antihistaminesmentioning
confidence: 88%
“…The effects of rupatadine in its therapeutic dose of 10 mg (Vuurman et al 2007) were also comparable to those of placebo treatment. Bilastine was tested in 20 and 40 mg doses, both after acute dosing and repeated doses, and was found not to cause driving impairment in any of these dosing conditions (Conen et al 2010).…”
Section: Second Generation Antihistaminesmentioning
confidence: 99%
“…Similar findings have been reported before. 1,33,56 It underscores the notion that users of hydroxyzine should receive explicit warnings about these drugs' deleterious effects on cognitive performance regardless of time of dosing.…”
Section: Discussionmentioning
confidence: 99%
“…None of the conducted clinical trials showed any influence of bilastine on the morphology of the ECG signal and QTc interval. Thus, it could be stated that the cardiovascular safety of bilastine is very high, and the influence of the drug on morphology of the ECG signal and cardiac muscle repolarization is the same as that of placebo [10,15,[32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Cardiovascular Safety Of Antihistaminesmentioning
confidence: 99%